1999
DOI: 10.1680/macr.1999.51.4.255
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rapid cooling by water quenching on the stiffness properties of fire-damaged concrete

Abstract: This paper reports the results of experimental research into assessing the fractured state of fire-damaged concrete under rapid cooling in an attempt to establish the effects of fire-fighting operations on the structural integrity of concrete buildings subject to a fire. The investigation was driven by the need to improve the material models used in predicting the fire resistance of concrete members or redesigning such members after a fire incident. The extent of damage was quantified using the stiffness damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Figure 9 shows that the strain at failure of quenched concrete is more than that of air-cooled concrete. This is a further evidence [11] of the disruption and damage caused by spraying hot concrete with cold water. However, the effect is more pronounced the higher the temperature experienced.…”
Section: Resultsmentioning
confidence: 63%
“…Figure 9 shows that the strain at failure of quenched concrete is more than that of air-cooled concrete. This is a further evidence [11] of the disruption and damage caused by spraying hot concrete with cold water. However, the effect is more pronounced the higher the temperature experienced.…”
Section: Resultsmentioning
confidence: 63%
“…The peak temperatures of 400, 500, 550, and 600 1C, and the exposure times of 0, 1, and 2 h were adopted in experiment. The studies performed by Nassif et al [8] investigated the temperature distribution in a concrete core at elevated temperature and it was found that there is no temperature difference in the concrete core soon after the heating temperature reaches the peak temperature. After exposing to the elevated temperature, the concrete specimens were cooled down in the ambient air (natural cooling) and tested at 7, 30, 90, and 180 days after heating.…”
Section: Experimental Specimensmentioning
confidence: 99%
“…The use of ultrasonic pulse velocity (UPV) for assessment of concrete residual strength is one of the most interesting subjects in the field of nondestructive testing of concrete after exposure to high temperatures. Several experimental studies had been carried out to investigate how the pulse velocity was affected by the damage of concrete caused by various high temperatures [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Nassif et al [20] have examined degradation of Youngs modulus of concrete. Cylindrical specimens, 75 mm in diameter and 175 mm in height, were used.…”
Section: Figmentioning
confidence: 99%